Smart monitoring and automatic plant watering for agriculture - Jumaat, Siti Amely; Ashari, Ahmad Asraf; Abd Azi, Anis Azma; Shariffuddin, Ahmad Azhar Ashraf; Ahmad Wizan, Anas Syafiq; Ghazali, Eizaz Ahmad; Martin, Belinda (Penerbit UTHM, 2020)
Nowadays agriculture depends on engineering and technology especially for increasing the production and reducing the manpower. Good irrigation system, drainage system and consideration of the nature conservation are known as the important key in successful farming either in the business field or management as the work become more efficient with the existence of the engineering system and planning. Plants are very beneficial to the living things in many aspects such as giving a hand to balance the environment by cleaning the air naturally and also producing oxygen for man and animals daily usage. These plants are dependent on conventional breeding - watering based on their species and the right amount or exposure of the sun to sustain its life and growth. Besides, plants are one of the living things that give a big impact through the ecosystem by maintaining the climate change and provided food. Water is a main component for the development of plants in agriculture or irrigation. The amount of water received by the plant should be measured according to the requirement of the species, the type of the soil used for the plant and the considering of the weather...